Young People as City Builders: Youth Participation in German Municipalities. Issue 1 (2nd January 2016) - Heinrich, Anna Juliane; Million, Angela
Abstract: In 2009 the German Federal Ministry of Transport, Building and Urban Development launched a research program called "Adolescents in Urban Neighborhoods" to foster youth participation in urban development and planning in Germany. In all, 55 pilot projects were funded and implemented across Germany to explore methods, instruments and strategies to involve youth in urban planning and decision-making processes between 2009 and 2013. To expand our understanding of what youth participation can be, chances and challenges of state-led participation and two further forms of engaging with participation are discussed and further defined in the paper: the integration of youth-led projects in planning processes and youth advocate-led participation.